Essays on the pricing behavior of firms using an agent-based modeling approach - Schiozer, Nikolas Alexander Van de Bilt (2023)
The pricing decision of firms plays a crucial role in determining the competitiveness of goods, company profits, and the macroeconomic impact on the economy. This thesis consists of a prologue and three essays that aim to provide insights into the pricing behavior of firms and its impact on the economy. The first essay presents an hybrid DSGE-ABM model that considers the limited information of firms about the market conditions and their continuous adaptation of pricing strategies. The second essay investigates the persistence of heuristic heterogeneity among firms and why they do not converge to a single optimal pricing heuristic. The third essay explores the issue of price stickiness from both micro and macroeconomic perspectives. The study argues that an evolutionary process of selection of pricing heuristics may play a role in explaining why firms tend to keep their prices as stable as possible. The findings contribute to the literature by providing insights into the pricing behavior of firms, highlighting the importance of considering heterogeneity among firms in macroeconomic models, and have implications for future research on the drivers of price adjustments and the impact of economic policy.